Mapping scholarly publications of energy conservation and emission reduction in support of the sustainable development goals (SDGs) - Xu, Kewei; Yang, Mingmei; Yang, Jiamiao; Nataliia, Butina; Cai, Yuanyuan; Zhang, Hao; Wang, Yanwen (Frontiers in Environmental Science, 2024)
In light of continuous advancements in science and technology, the global economy is experiencing rapid growth. However, this growth has been accompanied by significant depletion of natural resources and environmental degradation. Consequently, there is a burgeoning global emphasis on energy conservation, emissions reduction, and sustainable development. In this study, based on the Science Citation Index Expanded (SCIE) and Social Science Citation Index (SSCI) databases from 1990 to 2022, a statistical analysis of energy conservation and emission reduction in alignment with Sustainable Development Goals (SDGs)-related publications was undertaken using biblimometric methods. The findings reveal that (1) In recent years, there has been a discernible increase in global research on this subject, especially since 2009，with a sustained trend of exceeding 100 publications per annum. China prominently contributing to this domain, the proportion reached 34.2%, reflecting a growing emphasis on eco-friendly development trends. (2) Due to the burgeoning significance of energy conservation and emission reduction, there has been a notable escalation in research efforts pertaining to "Energy & Fuels", "Environmental Science" and "Green & Sustainable Science & Technology" and other related subjects. (3) Regarding the keyword analysis, "renewable energy" as the most frequently encountered term, often paired with "CO2 emissions". This association underscores the pivotal role of renewable energy technologies in advancing green development initiatives and mitigating emissions. (4) China, USA and UK occupy central positions in terms of both paper publication volume and collaborative networks, collectively accounting for about 54.7%, and these countries are pivotal contributors to the scholarly discourse on sustainable development and environmental conservation. (5) From 1990 to 2022, the top 20 cited articles predominantly address diverse sub-goals of SDG 7, with a common emphasis on enhancing energy efficiency, sustainability and renewable energy. These findings furnish valuable analytical insights for subsequent researchers investigating energy conservation and emission reduction as well as sustainable development endeavors.